Comparative evaluation of the effects of epidural morphine and 0.9% sodium chloride on cardiorespiratory function and anesthetic recovery in ponies - Natalini, Cláudio Corrêa; Crosignani, Nadia; Polidoro, Alexandre da Silva (Acta Scientiae Veterinariae, 2018)
Epidural analgesia is an effective technique to treat acute and chronic pain as well as to provide preemptive, intraoperative, and postoperative analgesia. This study was performed to evaluate the effects of epidurally injected morphine and a control group that received 0.9% sodium chloride. Eighteen healthy male adult ponies were studied. Two groups of 9 were formed. Group M (morphine) received 0.1mg/kg morphine diluted up to 5ml in sterile water, injected at the first intercoccygeal intervertebral space. Group S (saline) received 5ml of sterile 0.9% sodium chloride. All animals received 1mg/kg xylazine IV for sedation, were induced with 5% guaifenesin at 55mg/kg and 5% thiopental sodium at 4mg/kg IV, and maintained with halothane. Orthopedic surgeries on the thoracic limb (desmotomy) and on the pelvic limb (total ostectomy of the metatarsal II bone) were performed. After anesthesia induction, heart rate, respiratory rate, and arterial blood pressure recorded at 15 minutes intervals, for 90 minutes. Recovery times were recorded beginning when the administration of halothane was interrupted. Recovery quality was graded and compared between groups. Data was analyzed with two-way ANOVA and Bonferroni’s test, and ANOVA on ranks. Results demonstrated that recovery time was significantly shorter for the saline group, although the recovery quality was better for the morphine group. Epidural morphine does not produce surgical analgesia for the thoracic limbs in ponies. However it does produce for the pelvic limbs. Epidural morphine in ponies produces superior recovery quality when halothane is used as an inhalant anesthetic.